The right of access to public information as a mechanism of social control: Comparative analysis in five Latin American countries (2018)
The following study seeks to review the states of policies and the institutional development of them in the area of Transparency and Right of Access to the information in the region, to, once within the pertinent conceptualization where diverse sources about Accountability are consulted, generate a comparison that, subsequently, allows to identify which the conditions would be for the tools present in each of the analyzed countries, according to their own legislation, to allow the exercise of Accountability and the configuration of access to information as a right in itself and a way of social control to public management